2019
DOI: 10.1111/nan.12536
|View full text |Cite
|
Sign up to set email alerts
|

Review: Modelling the pathology and behaviour of frontotemporal dementia

Abstract: Frontotemporal dementia (FTD) encompasses a collection of clinically and pathologically diverse neurological disorders. Clinical features of behavioural and language dysfunction are associated with neurodegeneration, predominantly of frontal and temporal cortices. Over the past decade, there have been significant advances in the understanding of the genetic aetiology and neuropathology of FTD which have led to the creation of various disease models to investigate the molecular pathways that contribute to disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 228 publications
(317 reference statements)
1
12
0
Order By: Relevance
“…In fact, knocking down PPIA affected the expression of a number of TDP-43 target genes involved in pathways leading to neurodegeneration, including GRN. GRN has been found mutated in familial forms of FTD and the disease mechanism seems to be linked to GRN haploinsufficiency, as also confirmed in mouse models (Solomon et al, 2019). In the cortex of PPIA-/-mice, we found that GRN was downregulated, indicating that a GRN loss-of-function probably contributes to the development of an FTD phenotype in PPIA-/-mice.…”
Section: Ftld-tdp Is the Most Common Neuropathologic Type Of Ftld Andsupporting
confidence: 79%
See 2 more Smart Citations
“…In fact, knocking down PPIA affected the expression of a number of TDP-43 target genes involved in pathways leading to neurodegeneration, including GRN. GRN has been found mutated in familial forms of FTD and the disease mechanism seems to be linked to GRN haploinsufficiency, as also confirmed in mouse models (Solomon et al, 2019). In the cortex of PPIA-/-mice, we found that GRN was downregulated, indicating that a GRN loss-of-function probably contributes to the development of an FTD phenotype in PPIA-/-mice.…”
Section: Ftld-tdp Is the Most Common Neuropathologic Type Of Ftld Andsupporting
confidence: 79%
“…In previous work we demonstrated that PPIA deficiency affected the expression of a number of TDP-43 target genes, including GRN, which is a major mutated gene in familiar FTD (Lauranzano et al, 2015). GRN mutations in patients result in haplo-insufficiency and GRN knock-out mice present an FTD-like phenotype with mild TDP-43 pathology (Solomon et al, 2019). We verified whether knocking out PPIA influenced GRN expression in the brain cortex of the mice.…”
Section: Ppia Deficiency Downregulates Grn and Tardbp Expressionmentioning
confidence: 74%
See 1 more Smart Citation
“…These findings have contributed to shed light on the major biological processes altered in ALS and FTD/FTLD pathologies (Table 1) [29]. On the other hand, as the genes associated with these diseases were fleshed out, it was apparent that ALS and FTD share pathophysiological processes.…”
mentioning
confidence: 94%
“…Appropriate disease models are useful tools for testing hypotheses relevant for disease pathogenesis of FTLDs and will be essential for probing the efficacy of therapeutic approaches once they have become available. The article by Solomon, Mitchell, Konrad, Vance and Mizielinska provides a comprehensive and critical review of the in vivo models of distinct forms of FTLDs with an emphasis on disease models that replicate neuropathological and behavioural aspects of the human disease. It is particularly useful that the authors discuss separately two large groups of FTLD models, the genetic models ( GRN , C9orf72 , CHMP2B , VCP , UBQLN2 , SQSTM1 ) and models whose primary aim is to recapitulate directly the pathology of FTLD‐TDP or FTLD‐FUS.…”
mentioning
confidence: 99%